The Ostrich - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
All you ever wanted to know about these cute and tasty birds!Edited by D C Deeming. Hatchery Consulting and Research, and University of Manchester, UK. CABI. 1999. 360 pp.ISBN 0851993508£55 US$100 Euro 96.15CABI Publishing,Wallingford,...